Power and Good Governance: Observations from Nigeria - Columbus, Ogbujah (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2016)
In recent times, the terms ‘power’, ‘governance’ and ‘good governance’ are bandied around conferences, symposia and literary works that seek for solution to the multifaceted problems of modern life. This has become necessary, and perhaps expedient because while in some climes people legitimately struggle for power to rule, others in different regions usurp it through undemocratic means (by military coups); and others still, while hiding under democracy, unleash terror on the citizenry and/or political opponents in order to accomplish their personalized agenda unhindered. Today, Nigeria is ranked low in the committee of democratic nations because of lack of good governance: there is massive corruption, political turbulence, decline in economic productivity, and overall social discontent sometimes orchestrated by the activities of ethnic militia. The spate of violence and crimes has created an alarming sense of insecurity, such that people no longer trust on the powers of their government for protection. This paper has looked at the use of power by Nigerian political actors, especially during the democratic dispensation, and found that the flagrant disregard for the rule of law (abuse of power) has been the bane to good governance. It discovered that bad governance which is increasingly linked to corrupt ‘use of power’ is the root cause of social glitches within the nation.